HERS: Understanding the Reason Behind a Woman’s Choice not to Get Married - Gabriella Thiono (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This creative project is a screenplay. The screenplay is about a woman who struggles to defy the idea of getting married. In the New Order, President Soeharto led Indonesia using Javanese culture. Until today, there is a belief that women in Indonesia are obliged to get married because of the culture. In Javanese culture, there is a value called 3M (macak, masak, manak). The value created a definition of a true woman. A true woman has to be able to look pretty and cook. In order to fulfil the third value, a woman has to get married and have a family. This value burdens some modern Indonesian women, especially those who have careers. Through this screenplay, I want to encourage women that being married is a matter of choice and not an obligation. Keywords: Indonesian women, Javanese value, Javanese culture, marriage, single woman.